A folding decalin tetra-urea for transmembrane anion transport. Issue 33 (17th August 2017) - Valkenier, Hennie; Dias, Christopher M.; Butts, Craig P.; Davis, Anthony P.
Abstract: A new approach to anionophore design combines a trans -decalin scaffold with flexible o -phenylene bis-urea side-arms. The scaffold preorganises the side-arms, which can fold to encompass anionic substrates. A prototype has been synthesised by coupling an o -aminophenyl urea to a decalin bis-isocyanate, and has been shown to be active for anion binding and transport. Modelling and NMR studies show that the unbound receptor is capable of intramolecular hydrogen bonding but can reorganise to form up to eight hydrogen bonds to a chloride anion. Graphical abstract: